2021
DOI: 10.3390/cancers13020226
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of NK Cell Phenotype in the Disease Course of Multiple Myeloma

Abstract: Accumulating evidence demonstrates important roles for natural killer (NK) cells in controlling multiple myeloma (MM). A prospective flow cytometry-based analysis of NK cells in the blood and bone marrow (BM) of MM patient subgroups was performed (smoldering (SMM), newly diagnosed (ND), relapsed/refractory, (RR) and post-stem cell transplantation (pSCT)). Assessments included the biomarker expression and function of NK cells, correlations between the expression of receptors on NK cells with their ligands on my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…Accordingly, the most active drugs for MM treatment or for reducing the risk of evolution from sMM to MM include agents with strong activity on the microenvironment, such as immunomodulatory drugs (IMiDs) or monoclonal antibodies [10,11]. In this context, much evidence supports the critical role played by stromal cells [12,13] and different cells of the IM (such as dendritic cells [14], myeloid-derived suppressor cells (MDSCs) [15,16], natural killer [17], and specific lymphocytes subclasses including the pro-inflammatory Th17 cells [18,19]) as well as BM-extrinsic drivers such as the microbiota [20] in driving MM evolution. Gut microbiota, particularly by promoting chronic inflammation and/or immune suppression, could drive non-aerodigestive tract malignancies with mechanisms that are still under active investigation and have been recently identified as a new player in determining tumor progression [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the most active drugs for MM treatment or for reducing the risk of evolution from sMM to MM include agents with strong activity on the microenvironment, such as immunomodulatory drugs (IMiDs) or monoclonal antibodies [10,11]. In this context, much evidence supports the critical role played by stromal cells [12,13] and different cells of the IM (such as dendritic cells [14], myeloid-derived suppressor cells (MDSCs) [15,16], natural killer [17], and specific lymphocytes subclasses including the pro-inflammatory Th17 cells [18,19]) as well as BM-extrinsic drivers such as the microbiota [20] in driving MM evolution. Gut microbiota, particularly by promoting chronic inflammation and/or immune suppression, could drive non-aerodigestive tract malignancies with mechanisms that are still under active investigation and have been recently identified as a new player in determining tumor progression [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the importance of NK cells in MM control has been demonstrated in several studies [25][26][27]. Accordingly, NK cells from MM patients show both quantitative and qualitative changes compared to NK cells from healthy donors [28,29]. Taken together, this evidence paints a complex picture where progressive immunosuppression associates with MM development.…”
Section: Introductionmentioning
confidence: 67%
“…Still, lower baseline levels of CD16 correlate with decreased ADCC responses in NK cells: compared with NK cells obtained from healthy donors, it was demonstrated that NK cells from cancer patients showed a significant reduction of both direct killing and ADCC against tumors, which was due to CD16 down-regulation [ 58 ]. In cancer patients, the expression levels of CD16, DNAM-1, and NKG2D have also been reported down-regulation on NK cells [ 59 , 60 ]. A Western blot assay using NK cells after stimulation with tumor cells may further add proof to possible CD16 shedding.…”
Section: Discussionmentioning
confidence: 99%